Are Negotiation Strategies Worthwhile for Digital Public Relations and Effectiveness of Communication? A Conceptual Paradigm [?????????????????????????] - Mohammed Alhasani Y.R.; Bte Muslim N.A. (Hunan University, 2023)
Communication effectiveness; Conceptual frameworks; Digital public relation; Effective communication; Emerging technologies; Industry stakeholders; Model development; Negotiation strategy; Paradigm; Scientific methodology; Public relations